Propuesta de acciones correctivas para los riesgos laborales evaluados en la empresa Llano7Días - Villavicencio (2021)
The International Labor Organization (ILO) each year has estimated that “around 17 million people are victims of work accidents, this estimate is enormous and its economic burden due to poor safety and health practices in the year which goes in a 4% of annual gross domestic product, for this reason the ILO is promoting that companies handle prevention for their workers”(Robayo, 2017). However, companies are not having the necessary resources to care for the health and safety of their workers, which is why in 2015 Decree 1072 was issued in Colombia and in 2019 Resolution 0312 that “obliges all companies that have more than 10 employees to design and implement an Occupational Health and Safety Management System ”this under the minimum required standards; Therefore, this project seeks to carry out a diagnosis of the current state of the SG-SST of the Llano Siete Días newspaper in the city of Villavicencio, Meta; in order to design corrective measures taking into account the identification of risks and the ergonomic analysis that demonstrate the exposure of the working population to a possible occupational accident. It was carried out through an observational type of investigation, with a descriptive nature and the collection of data in a transversal way and according to the population and sample it is a census type investigation, implementing tools such as interviews, matrix, formats, and evaluative profiles. The results present the plan for corrective measures for the company Llano Siete Días in favor of improving the working conditions of each of the jobs.